PENERAPAN PENGENDALIAN INTERN DALAM RANGKA PENYUSUNAN LAPORAN KEUANGAN PADA DEPOT AIR MINUM ISI ULANG NOVA NESYA - Antonius Tandi; Revleen Kaparang; Sintje Alow; Lusye Kumaat; Heidy Rumambi; Lidya Maramis; Agung Eka Dewi; Regina Sahabati (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Depot Nova Nesya is a Water refilling business located in Tomohon City, North Sulawesi Province which support people’s economic empowerment, cash is the most current asset so cash is easily manipulated and misappropriated, so to secure cash receipts and disbursements an internal cash control system is needed, the research method is using qualitative research. The data collection technique is through interviews with Air Isi Ulang employees and literature studies on materialrelated to cash. Data analysis is carried out using the stages of data reduction, data presentation and drawing conclusions. The results of the research show that the control system internal cash management has not been carried out, such as there is no separation of functions, accounting records have not been carried out regularly and an organizational structure is not yet available The results of this research are recommendations for the Air Isi Ulang to make improvements in term of cash management.